Design of Sekolah Penggerak principal leadership in implementing best practices - Sutarjo, Sutarjo; Danim, Sudarwan; Somantri, Manap (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research aims to determine the leadership design of Sekolah Penggerak principals in instilling good practices in high schools in East OKU Regency. The method used in this research is research and development. The Research and Development (R&D) research procedure used in this research adopted the ADDIE model which consists of five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The results of the research show that the initial conditions for the development of Sekolah Penggerak for school principals in implementing good practices in SMA East OKU Regency still require adaptive school planning and management to adapt to current developments and ensure quality learning. The Sekolah Penggerak principal's leadership design in instilling good practices is presented in units such as the Sekolah Penggerak program, school operational management working group, mentoring activities by the principal, and mentoring of the principal. The feasibility of the leadership design was declared feasible to implement, with an average score of 83.4% on the feasibility criteria and 80.73% on the material validator. This research could be groundbreaking in understanding how school leadership can influence best practices in secondary schools and provide valuable new insights for educational practitioners, researchers, and policymakers. This research can make a significant contribution to our understanding of how school leadership can improve best practices at the high school level, as well as provide a foundation for further research in this area.